2021
DOI: 10.1038/s41598-021-93554-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of optimal continuous positive airway pressure in Thai patients with obstructive sleep apnea

Abstract: Continuous positive airway pressure (CPAP) is simple and effective treatment for obstructive sleep apnea (OSA) patients. However, the CPAP prediction equation in each country is different. This study aimed to predict CPAP in Thai patients with OSA. A retrospective study was conducted in Thai patients, who OSA was confirmed by polysomnography and CPAP titration from January 2015 to December 2018. Demographics, body mass index (BMI), neck circumference (NC), Epworth sleepiness scale, apnea–hypopnea index (AHI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…Our results declared that minSpO 2 was also an independent predictor for optimal value of CPAP. This was similar to several previous studies [16,23,24,29]. Oxyhemoglobin desaturation during sleep is directly related to the duration of apnea and indirectly to end-tidal lung volume at the beginning of apnea, without considering other causes such as lung diseases and/or hypoventilation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results declared that minSpO 2 was also an independent predictor for optimal value of CPAP. This was similar to several previous studies [16,23,24,29]. Oxyhemoglobin desaturation during sleep is directly related to the duration of apnea and indirectly to end-tidal lung volume at the beginning of apnea, without considering other causes such as lung diseases and/or hypoventilation.…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that BMI were the most important independent predictors of optimal value of CPAP [22]. Extensive clinical researches have shown that BMI was one of the independent factors affecting the optimal CPAP [16,[23][24][25] (Table 4). AHI is the gold standard for the diagnosis and severity classification of OSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 26 ] Thereafter, several reports suggested similar results in Caucasian, Asian, and mixed populations. [ 17 37 38 39 40 41 ] In this study, the number of respiratory events per hour of NREM sleep was a predictor of the optimal PAP requirement when considered independently but not during multivariable analyses. Although the AHI has been used for decades to define OSA severity in research and clinical practice,[ 1 ] it captures a single aspect of OSA severity (i.e., the number of respiratory events) and ignores many other aspects (e.g., the length and type of events), which renders its reliability questionable.…”
Section: Discussionmentioning
confidence: 78%
“…In the current study, deoxygenation indices allowed a better prediction of the optimal PAP requirement when multiple variables were analyzed, and this was also noted in earlier reports. [ 40 41 47 48 49 ] The arousal index was selected for inclusion in our PAP prediction equation. We found no previous studies reporting the inclusion of indices of arousal disturbance during sleep in PAP prediction equations.…”
Section: Discussionmentioning
confidence: 99%